2013
DOI: 10.1155/2013/825437
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Livestock Ammonia Emission under the Changing Temperature during the Initial Manure Nitrogen Biomineralization

Abstract: Experimental data were applied for the modelling optimal cowshed temperature environment in laboratory test bench by a mass-flow method. The principal factor affecting exponent growth of ammonia emission was increasing air and manure surface temperature. With the manure temperature increasing from 4°C to 30°C, growth in the ammonia emission grew fourfold, that is, from 102 to 430 mg m−2h−1. Especial risk emerges when temperature exceeds 20°C: an increase in temperature of 1°C contributes to the intensity of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, reducing the temperature inside barns is one of the proposed strategies to increase the activity of microbes responsible for reducing the gaseous NH 3 concentration and nuisance odor [45]. McCrory et al suggested that higher temperatures inside storage barns favor the dominant pathway of NH 3 production [43], and Bleizgys et al [46] stated that reducing the temperature inside barns could be an excellent way to reduce NH 3 emissions. The above strategies align with the results of the current study, as seaweed masking decreased the barn temperature, consequently reducing gaseous NH 3 and amine emissions and eliminating the nuisance odor.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, reducing the temperature inside barns is one of the proposed strategies to increase the activity of microbes responsible for reducing the gaseous NH 3 concentration and nuisance odor [45]. McCrory et al suggested that higher temperatures inside storage barns favor the dominant pathway of NH 3 production [43], and Bleizgys et al [46] stated that reducing the temperature inside barns could be an excellent way to reduce NH 3 emissions. The above strategies align with the results of the current study, as seaweed masking decreased the barn temperature, consequently reducing gaseous NH 3 and amine emissions and eliminating the nuisance odor.…”
Section: Discussionmentioning
confidence: 99%
“…Lowering the cow barn temperature and the airflow rate above the manure surface [4][5][6], as well as cutting the manure-soiled area [7; 8] may reduce the ammonia emissions. The laboratory tests have verified the effect of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory tests have verified the effect of these factors. It was established that higher air and manure surface temperature resulted in an exponential increase in ammonia emissions [5], while the dependence of emission on the air velocity was best expressed by a second-degree polynomial [4]. At the same time, excessive ventilation reduction leads to the indoor air quality degradation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sutton et al (2013) concluded from the results of various field campaigns that the percentage of N volatilized as ammonia increased exponentially as a function of average temperature Bleizgys et al (2013). also found similar correlations from experiment results from a naturally ventilated open cowshed lab, namely, ammonia increased emission gains at higher temperatures.…”
mentioning
confidence: 57%